Coleus bolavenensis (Lamiaceae), a new species from Laos - Suddee, Somran; Tagane, Shuichiro; Souladeth, Phetlasy; Kongxaysavath, Deuanta; Rueangruea, Sukid; Suyama, Yoshihisa; Suzuki, Eizi (Thai Forest Bulletin (Botany), 2020)
Coleus bolavenensis, a new species from Bolaven Plateau, southern Laos is described and illustrated. A preliminary conservation status is provided.